2018
DOI: 10.1590/s0102-053620180412
|View full text |Cite
|
Sign up to set email alerts
|

Fruit yield and gas exchange in bell peppers after foliar application of boron, calcium, and Stimulate

Abstract: The objective of this study was to evaluate the effect of the isolated and combined foliar application of boron, calcium, and the plant growth regulator Stimulate on fruit yield and gas exchange in bell peppers. The evaluated treatments were boron, calcium, Stimulate, boron + calcium, boron + Stimulate, calcium + Stimulate, boron + calcium + Stimulate, and control (water). The study was performed in complete randomized block design with three replicates. The applications were performed biweekly on the plant le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…This physiological effect promoted by biostimulants was reported in a recent study with greenhouse-grown peppers, in which the application of a biostimulant based on algae extract (0.5%) led to a 27% increase in stomatal conductance, resulting in the highest *, **, and ns = significant at p ≤ 0.05, significant at p ≤ 0.01, and not significant, respectively, by the F-test; y 0 = 0 kg ha -1 of humic substances; y 8 = 8 kg ha -1 of humic substances; y 12 = 12 kg ha -1 of humic substances; Means with different letters are not significantly different from each other by the Tukey's test (p ≤ 0.05) production obtained in the study: 314 kg per 1000 plants (Melo et al, 2020). Zeist et al (2018) reported an increase of 18.96% in transpiration rate of pepper plants grown under application of a biostimulant composed of plant phytohormones, which was a result lower than that found in the present study (42.4%). Furthermore, humic substances can affect other metabolic pathways, such as respiration, as they can activate specific genes related to enzymes like glucose-6 phosphate-isomerase and pyruvate kinase in the respiratory metabolic process (Nardi et al, 2021).…”
Section: Resultsmentioning
confidence: 71%
“…This physiological effect promoted by biostimulants was reported in a recent study with greenhouse-grown peppers, in which the application of a biostimulant based on algae extract (0.5%) led to a 27% increase in stomatal conductance, resulting in the highest *, **, and ns = significant at p ≤ 0.05, significant at p ≤ 0.01, and not significant, respectively, by the F-test; y 0 = 0 kg ha -1 of humic substances; y 8 = 8 kg ha -1 of humic substances; y 12 = 12 kg ha -1 of humic substances; Means with different letters are not significantly different from each other by the Tukey's test (p ≤ 0.05) production obtained in the study: 314 kg per 1000 plants (Melo et al, 2020). Zeist et al (2018) reported an increase of 18.96% in transpiration rate of pepper plants grown under application of a biostimulant composed of plant phytohormones, which was a result lower than that found in the present study (42.4%). Furthermore, humic substances can affect other metabolic pathways, such as respiration, as they can activate specific genes related to enzymes like glucose-6 phosphate-isomerase and pyruvate kinase in the respiratory metabolic process (Nardi et al, 2021).…”
Section: Resultsmentioning
confidence: 71%
“…Although most of these researches has observed positive results on seedlings development, those that link its use to final crop yield are still incipient, although it is known that it is a practice that raises the production cost. Positive results on crop yield have already been reported for grafted peppers of the Golden and Zarco hybrids (PALANGANA et al, 2012), but no effect was observed for the All Big cultivar (ZEIST et al, 2018). In rocket its use promoted an increase in production of the Rokita cultivar, but not in the Folha Larga cultivar (SILVA et al, 2018).…”
Section: Resultsmentioning
confidence: 93%
“…Bell pepper cultivation is usually difficult and fruit production is not always satisfactory. Nitrogen and potassium are some of the nutrients most extracted by bell pepper plants, which contribute to plant growth and fruit quality (Felisberto et al, 2016;Zeist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%